Experimental evaluation of an innovative command for hydronic radiant heating floors - Silva, Pedro Dinho da (2019)
This paper presents the results of an innovative control, regulation and command system for hydronic radiant floors, more flexible and efficient that guarantees a better thermal comfort to the user and simultaneously improves the energy efficiency of this type of heating system. The control algorithm is based on the calculation of PMV (Predicted Mean Vote) index as defined on Thermal Comfort Standard ISO 7730. To improve energy efficiency, the control algorithm was implemented on a microcontroller system that fea-tures wireless communication with sensors modules powered by energy harvesting systems. The experimental tests were performed in a hydraulic underfloor built into a laboratorial climatic chamber. The results show that for a water inlet of 35 ºC, the controller turn the valve on/off less than other control systems in order to adjust the PMV while maintaining the floor surface temperature less than 29 ºC as recommended by international standards.